2002
DOI: 10.1128/aac.46.5.1417-1424.2002
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of KatG Ser315Thr Substitution among Isoniazid-Resistant Mycobacterium tuberculosis Clinical Isolates from Northwestern Russia, 1996 to 2001

Abstract: A total of 204 isoniazid (INH)-resistant strains of Mycobacterium tuberculosis isolated from different patients in the northwestern region of Russia from 1996 to 2001 were screened by a PCR-restriction fragment length polymorphism (RFLP) assay. This assay uses HapII cleavage of an amplified fragment of the katG gene to detect the transversion 315AGC→ACC (Ser→Thr), which is associated with INH resistance. This analysis revealed a 93.6% prevalence of the katG S315T mutation in strains from patients with both new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
113
5
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(147 citation statements)
references
References 35 publications
25
113
5
4
Order By: Relevance
“…In contrast, but perhaps not unexpectedly given its highly complex mechanism of action, the mutations causing INH resistance are located in more than three genes and regions (Barry et al, 1998;Slayden & Barry, 2000). Depending on the sample set analysed, it has been reported that 50-95 % of INH-resistant strains contain mutations in codon 315 of the katG gene encoding the catalase-peroxidase (Mokrousov et al, 2002;Musser et al, 1996;Piatek et al, 2000;Telenti et al, 1997) and 20-35 % harbour mutations in the inhA promoter region (Musser et al, 1996;Piatek et al, 2000;Telenti et al, 1997). Moreover, 10-15 % of INH-resistant strains have mutations in the oxyR-ahpC intergenic region, although there is no direct evidence relating mutation at this region and INH resistance (Piatek et al, 2000;Telenti et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, but perhaps not unexpectedly given its highly complex mechanism of action, the mutations causing INH resistance are located in more than three genes and regions (Barry et al, 1998;Slayden & Barry, 2000). Depending on the sample set analysed, it has been reported that 50-95 % of INH-resistant strains contain mutations in codon 315 of the katG gene encoding the catalase-peroxidase (Mokrousov et al, 2002;Musser et al, 1996;Piatek et al, 2000;Telenti et al, 1997) and 20-35 % harbour mutations in the inhA promoter region (Musser et al, 1996;Piatek et al, 2000;Telenti et al, 1997). Moreover, 10-15 % of INH-resistant strains have mutations in the oxyR-ahpC intergenic region, although there is no direct evidence relating mutation at this region and INH resistance (Piatek et al, 2000;Telenti et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the case of rifampicin resistance, hundreds of rpo B mutations have been described (not all were associated with rifampicin resistance), but more than 80% of rifampicin‐resistant isolates display mutations in three codons rpo B531, 526 and 516 (Campbell et al., 2011; Lipin et al., 2007; Pozzi et al., 1999; Telenti et al., 1993). Similar to that, among the approximately 300 mutations found in the kat G gene, the prevalence of kat G S315T mutation can vary between 32% and 95% in isoniazid‐resistant clinical isolates depending on the geographic regions and drug resistance patterns (Hazbon et al., 2006; Lipin et al., 2007; Mokrousov et al., 2002; Vilcheze & Jacobs, 2014). …”
Section: Characteristics and Diversity Of Drug Resistance‐associated mentioning
confidence: 99%
“… Notes aNucleotide change.bSee the following studies for reference (Campbell et al., 2011; Duong et al., 2009; Hazbon et al., 2006; Hillemann et al., 2005; Lipin et al., 2007; Mokrousov et al., 2002; Müller et al., 2011; Niehaus et al., 2015; Perdigao et al., 2010; Pozzi et al., 1999; Qian et al., 2002; Shi et al., 2011; van Soolingen et al., 2000; Sreevatsan et al., 1996, 1997; Telenti et al., 1993; Von Groll et al., 2009). …”
Section: Characteristics and Diversity Of Drug Resistance‐associated unclassified
See 2 more Smart Citations